Vegetative part of Nigella sativa L. potential antineoplastic sources against Hep2 and MCF7 human cancer cell lines. Issue 1 (31st December 2023) - Aftab, Arusa; Yousaf, Zubaida; Rashid, Madiha; Younas, Afifa; Yasin, Hamna; Riaz, Nadia; Mansoor, Qaisar
Abstract : Cancer, a global health problem due to its increasing prevalence coupled with high mortality rate. Chemotherapy is an aggressive form of drug therapy. Herbal therapy is safer and healthier to treat specific medical issues. Nigella sativa has been used as traditional medicine for centuries. The crude oil extracted from seed is effective against diseases but vegetative part of N. sativa has always been ignored for its therapeutic potential. Hence, it was hypothesized that vegetative part could be potential antineoplastic source against cancer. Therefore, reactive oxygen species determination and antineoplastic activity were performed against Hep2 and MCF7 cancer cell lines. n-butanol extract of Vegetative Part (VP) caused maximum cell death of Hep2 (58% cell viability). The chloroform VP extract showed 38% cell viability at 10 mg mL -1 . The extracts with significant activity were later on validated through GCMS and LC-MS, following literature in PubChem, NIST and Spectrabase libraries.